Development of electrochemical sensors for the detection of photosystem inhibiting herbicides - Giannoudi, Louisa (Cranfield University, 2005)
The objective of the present work is the development of an amperometric sensor for detection of hydrogen peroxide and its integration with spinach chloroplasts for the further development of a sensor for herbicides. The design of the sensor employed screen- printing electrodes which are easily produced at the facilities available in Cranfield University. The hydrogen peroxide sensor has been based on horseradish peroxidase (HRP) as the catalytic element and hydroquinone as the mediator. HRP has been immobilised onto the sensor surface using a newly developed thioacetale-based polymer capable of covalent immobilisation of primary amines. A new HRP-based biosensor was screen-printed using a carbon/polymer mixture. Hydrogen peroxide concentrations were analysed at the reduction potential of hydroquinone (–0.3 V). The biosensors developed in this work had low detection limit of HB2BOB2B (0.1 µM), long term stability (they can be stored for 2 months at 4 P 0 PC) and good reproducibility of measurements (RSD ~ 5%). The hydrogen peroxide sensor has been further integrated with spinach chloroplasts in an attempt to create a sensor for photosynthesis-inhibiting herbicides. It was found however that the quantity of HB2BOB2B generated by chloroplasts in our experimental conditions was not sufficient to allow quantitative analysis. Due to this we have developed an alternative approach based on the electrochemistry of the Hill reaction. In this reaction the photosynthetic process and electron flow passing through photosystem II (PSII) is monitored through the quantity of reduced artificial electron acceptor. Upon illumination of the chloroplasts a signal from a reduced acceptor or mediator was recorded chronoamperometrically. The added herbicide inhibits the photosynthetic process and decreases the reduction of mediator. The decrease in measured current which is proportional to herbicide concentrations have been used for herbicide detection. Three mediators of Hill reaction were tested including 2,6 dichlorophenolindophenol (DCPIP) duroquinone and potassium ferricyanide. The optimal results were obtained using DCPIP. The optimal wavelength for the excitation of chloroplasts was 650 nm. The chloroplasts have been immobilised onto the sensor surface using cross-linking with glutaraldehyde and bovine serum albumin. The developed system allowed reliable detection of herbicides (RSD = 10%) with a detection limit of 1-8 nM depending on the type of herbicide. The sensor can be stored for 3 months at -80 P 0 PC. Preliminary measurements of river water samples using this sensor were also performed indicating good correlation between the data obtained with GC-MS and the chloroplast-based biosensor developed in this study.